Metabolic Factors in Cognitive Impairment and Depression - Smith, K (Innov Aging, 2018)
Depression and cardiometabolic dysregulation are independently associated with a high risk of dementia. This study aimed to examine the association of comorbid depressive symptoms and cardiometabolic dysregulation with risk of dementia. The sample comprised 4859 participants aged 50 or older without baseline dementia from the English Longitudinal Study of Ageing. Depressive symptoms were assessed using the Center for Epidemiologic Studies-Depression tool. Cardiometabolic dysregulation was defined as three or more cardiometabolic risk factors (systemic inflammation, central obesity, raised triglycerides, low high-density lipoprotein cholesterol, hypertension and hyperglycaemia or diabetes). Participants classified into four groups based on presence of depressive symptoms and cardiometabolic dysregulation. Results were analysed using Cox Proportional Hazards Regression adjusted for covariates. A total of 216 cases of incident dementia were reported over 10 years of follow-up. The group with high depressive symptoms only had an increased hazards of developing incident dementia during follow-up (HR 2.68, 95% CI [1.70 - 4.23]). This association remained significant after controlling for sociodemographics, lifestyle and cardiovascular comorbidity but was attenuated after adjustment for baseline cognition. No evidence was found for an association of overall cardiometabolic dysregulation with incident dementia, though sensitivity analyses revealed some individual components of cardiometabolic dysregulation with depressive symptoms (hyperglycemia, hypertension and abdominal obesity) had an unadjusted association with incident dementia. There is likely a complex relationship between depression and individual components of cardiometabolic dysregulation with dementia. More work needs to determine how combined and individual cardiometabolic abnormalities and depression influence dementia.